Association of DAT1 genetic variants with habitual sleep duration in the UK Biobank. Issue 1 (8th October 2018) - Rhodes, Jessica A; Lane, Jacqueline M; Vlasac, Irma M; Rutter, Martin K; Czeisler, Charles A; Saxena, Richa
Abstract: Short sleep duration has been linked to negative health effects, but is a complex phenotype with many contributing factors, including genetic. We evaluated 27 common single nucleotide polymorphisms (SNPs) in candidate genes previously reported to be associated with other sleep variables for association with self-reported habitual sleep duration in the UK Biobank in 111 975 individuals of European ancestry. Genetic variation in DAT1 (rs464049) was significantly associated with sleep duration after correction for multiple testing ( p = 4.00 × 10 −5 ), whereas SNPs correlated to a previously studied variable number tandem repeat (VNTR) in DAT1 were not significant in this population. We also replicated a previously reported association in DRD2 . Independent replication of these associations and a second signal in DRD2 (rs11214607) was observed in an additional 261 870 participants of European ancestry from the UK Biobank. Meta-analysis confirmed genome-wide significant association of DAT1 rs464049 (G, beta [standard error, SE] = −0.96 [0.18] minutes/allele, p = 5.71 × 10 −10 ) and study-wide significant association of DRD2 (rs17601612, C, beta [SE] = −0.66 [0.18] minutes/allele, p = 1.77 × 10 −5 ; rs11214607, C, beta [SE] = 1.08 (0.24) minutes/allele, p = 1.39 × 10 −6 ). Overall, SNPs in two dopamine-related genes were significantly associated with sleep duration, highlighting the important link of the dopamine system with adult sleep duration in humans.